The Influence of Situational Leadership on Employee Work Productivity with Work Environment as a Mediating Variable At BUMN Defense Industry (Study at PT Len Industri Persero) - Anggraeni, Yovita; Z, Faizal Mulia; Saori, Sopyan (Utan Kayu Publishing, 2024)
This study aims to analyze the effect of situational leadership on employee productivity with work environment as a mediating variable at PT Len Industri (Persero), a state-owned enterprise in the defense industry sector. The research method used is quantitative method with associative approach. Data were collected through questionnaires distributed to employees of PT Len Industri (Persero). The research sample was taken using the slovin formula, with a total of 220 respondents. Data analysis was carried out using Structural Equation Modeling (SEM) with the help of PLS version 3 software. The results showed that situational leadership has a significant influence on employee work productivity by 3.037. In addition, it was found that work environment acts as a significant mediating variable in the relationship between situational leadership and employee work productivity by 5.980. This means that effective situational leadership can increase employee work productivity directly, as well as through improving the quality of the work environment. This research provides a practical contribution for PT Len Industri (Persero) in implementing an adaptive leadership style and creating a conducive work environment to increase employee work productivity.